2014
DOI: 10.1261/rna.043026.113
|View full text |Cite
|
Sign up to set email alerts
|

miR-19b promotes tumor growth and metastasis via targeting TP53

Abstract: Tumor suppressor TP53 (or p53) is one of the most important regulators in numerous physiological and pathological processes. Recently, the miRNA-mediated post-transcription regulation of p53 has been studied. However, systematic studies of miRNA targeting sites within the p53 gene are still a challenging task. Here, we developed a dual-color assay capable of identifying miRNA targeting sites in a certain gene, specifically p53, in a simple, direct, and robust manner. Results showed that p53 was a direct and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 24 publications
1
52
0
1
Order By: Relevance
“…42,[49][50][51][52][53][54][55][56][57] In addition, miR-19 upregulation was observed in various cancers including lung cancer, and correlated with tumor metastasis and/or poor prognosis of cancer patients. [11][12][13][14][15]18 Given that miRNAs primarily function through inhibiting the translation of their mRNA targets, we propose that miR-19 might be a negative regulator for PTEN, which has been reported by other researchers. 10,29,58,59 In addition, miR-19 increased the resistance to apoptosis of mouse B-cell lymphoma, 10,29 and chemoresistance of human breast cancer 58 and gastric cancer 59 through directly repressing PTEN expression.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…42,[49][50][51][52][53][54][55][56][57] In addition, miR-19 upregulation was observed in various cancers including lung cancer, and correlated with tumor metastasis and/or poor prognosis of cancer patients. [11][12][13][14][15]18 Given that miRNAs primarily function through inhibiting the translation of their mRNA targets, we propose that miR-19 might be a negative regulator for PTEN, which has been reported by other researchers. 10,29,58,59 In addition, miR-19 increased the resistance to apoptosis of mouse B-cell lymphoma, 10,29 and chemoresistance of human breast cancer 58 and gastric cancer 59 through directly repressing PTEN expression.…”
Section: Discussionsupporting
confidence: 71%
“…10 More recent studies have reported that miR-19a or miR-19b-1 promoted the migration and invasion of cervical carcinoma cells, 16 colon cancer cells, 17 and gastric cancer cells through targeting the tumor suppressor MXD1, 14 and Hela, MCF7, and Huh7 cells through targeting TP53. 18 Taken together, these results support that miR-19 is involved in cancer invasion and metastasis; however, the underlying mechanisms remain largely unknown.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Inhibitory effect of PPARα on glioma cell proliferation is blocked by targeting regulation of miR‐19, progression of tumour is enhanced 37. p53 has also been identified to be the target gene of miR‐19 in Hela cell 40. In glioma, expression of p53 is correlated negatively with that of miR‐19 31.…”
Section: Mir‐19 In Gliomamentioning
confidence: 99%